Politik Identitas Islam dan Urgensi Pendidikan Multikultural - Muthohirin, Nafik (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This article highlights the politics of Islamic identity that appears through persecution and religious-based violent extremism. During the past two decades, the hustle and bustle of public space seem to be filled with various religious symbols, which visibly deep respect for the reality of diversity while reducing the critical role of Pancasila as the ideology of the Indonesian state. If such behaviour is carried out in a corridor that upholds the values of Pancasila, then that attitude is not a problem. However, because the imposition of Islamic identity is accompanied by expressions of hatred and other judgmental attitudes, this needs to be anticipated. In fact, in several cases, this other judgmental attitude often leads to the mobilization of the masses to execute those who are considered different from the majority. Such a social situation can tear the religious plurality that has fostered this nation for a long time. Therefore, this article seeks to examine several things, namely: (1) tracking various acts of intolerance based on the politics of religious identity; (2) agencies that play an essential role in the occurrence of acts of persecution; (3) rethinking the urgency of multicultural education.Keywords. Identity Politics; Islam; Multiculturalism; Execution.